SEXUAL DYSFUNCTION AMONG FEMALE PATIENTS OF RHEUMATOID ARTHRITIS: AN UNDER ADDRESSED PHENOMENON - Hussain, Muhammad Zahid; Fakhr, Amer; Mumtaz, Naila; Cheema, Ahmed Ammar; Maqsood, Syed Uzair; Sajid, Yasmeen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the sexual dysfunction among the patients of rheumatoid arthritis and assess the relationship of various factors with presence of sexual dysfunction among the target population.Study Design: Cross sectional study.Place and Duration of Study: Rheumatology department, Pak Emirates Military Hospital Rawalpindi Pakistan, from Aug 2019 to Apr 2020.Methodology: The sample population comprised of 350 married female patients of rheumatoid arthritis between the age of 18 and 45 years, reporting for the routine follow-up at rheumatology department a tertiary care hospital. Sexual function was assessed using the female sexual function index (FSFI). Relationship of age, duration of rheumatoid arthritis, presence of comorbidities and polypharmacy was assessed with the sexual dysfunction among the target population.Results: Mean age of the study participants was 31.15 ± 4.22 years. Out of 350 women suffering from rheumatoid arthritis screened through female sexual function index, 172 (49.1%) had normal sexual function while 178 (50.9%) had sexual dysfunction. After applying the chi-square test, we found that polypharmacy and long duration of illness had significant association with the sexual dysfunction.Conclusion: High reporting of sexual dysfunction among the women suffering from rheumatoid arthritis indicates that this has been a neglected phenomenon by the physicians and researchers and may be added in routine screening. Women with long duration of illness and those managed with more than one drugs should be focused more while screening for sexual problems.